Membangun Kesadaran Tindakan Anti Bullying Siswa SD Negeri 2 Belor - Lufianti, Anita; Fitriani; Yuwanti; Nur Widayati, Christina; Rahmawati; Ragil Kusumaningrum, Yesita; Agustiana, Mika; Unggul Widodo, Wahyu; Novitasari, Dewi; Puspita Rini, Dea; Iffani Khoirunisa, Nur; Fitriyani, Nurul (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction : The phenomenon of bullying that occurs in kids often involves agrresive behavior that can be repeated by a certain person or group against other individuals who are considered or have weaknesses so that they are unable to defend themselves. Objective: The purpose of this service is to build awareness of anti-bullying actions in elementary schools, negative impacts and tolerance attitudes in children Method: This public service was conducted by counseling method with lectures, discussions, role simulations so that it can provide a real picture and effective ways to prevent it in elementary school children. Result:. This activity resulted in an increase in participants' understanding of the impact of bullying and simple and effective steps to prevent bullying. Conclusion: The community service that has been carried out contributes to creating a safer elementary school environment for children and supports mental well-being for the school